2016
DOI: 10.1038/srep36178
|View full text |Cite
|
Sign up to set email alerts
|

Responses of bacterial community structure and denitrifying bacteria in biofilm to submerged macrophytes and nitrate

Abstract: Submerged macrophytes play important roles in constructed wetlands and natural water bodies, as these organisms remove nutrients and provide large surfaces for biofilms, which are beneficial for nitrogen removal, particularly from submerged macrophyte-dominated water columns. However, information on the responses of biofilms to submerged macrophytes and nitrogen molecules is limited. In the present study, bacterial community structure and denitrifiers were investigated in biofilms on the leaves of four submerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 53 publications
2
44
1
Order By: Relevance
“…Compared with conventional denitrifying bacteria, Flavobacterium species can grow well and exhibit denitrification activity under aerobic conditions. Moreover, most of these strains are able to degrade organic matter via heterotrophic nitrification and metabolic activities [34,35]. In the present study, we found that Limnohabitans sp.…”
Section: Discussionsupporting
confidence: 53%
“…Compared with conventional denitrifying bacteria, Flavobacterium species can grow well and exhibit denitrification activity under aerobic conditions. Moreover, most of these strains are able to degrade organic matter via heterotrophic nitrification and metabolic activities [34,35]. In the present study, we found that Limnohabitans sp.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, formerly reported differences in phosphate concentrations (Hafouzov, ) cannot be supported by our data. Interestingly, nitrate, which we hypothesized would influence bacterial communities, is negatively correlated with strontium but had no significant effect on either the composition or diversity of bacterial communities, which is in contrast to results reported from other studies (Ben Maamar et al., ; Carrino‐Kyker, Smemo, & Burke, ; Ibekwe, Ma, & Murinda, ; Turlapati et al., ; Zhang et al., ). Nitrate might thus either not be a discriminating factor for the variation in BCC, or the effect of strontium overrides the effect of nitrate.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the postulated roles of the most abundant bacteria in morel substrates, members from the genus Pseudomonas are posited to be involved in morel fructification as further discuss in next section (Liu et al, 2017;Noble et al, 2009). Other dominant genera from the phyla Proteobacteria, Geobacter and Rhodoplanes, could help to degrade organic compounds into carbon sources available for the morels (Berlemont and Martiny, 2015) and enhance the availability of metal ions such as iron and manganese for fungi and plants through metal-reducing activity and siderophore production (Jin et al, 2013;Kügler et al, 2019) or simply they are denitrifying bacteria that thrive in the presence of fungal exudates (Zhang et al, 2016a). Species from the phylum Acidobacteria have been described to play an important role in maintaining the acidic pH value of the soil and therefore, also influence the uptake of trace elements from substrates, whereas bacteria belonging to the phylum Bacteroidetes have been reported to have the capacity to degrade cellulose and chitin (Liu et al, 2017).…”
Section: Cultivated Ascomycetes On Soilmentioning
confidence: 99%